A weight-based clustering multicast routing protocol for mobile ad hoc networks. (4th August 2005) - Huang, Chun-Chieh; Guo, Ming-Huang; Chang, Ruay-Shiung
In mobile ad hoc networks, the mobile nodes can move arbitrarily without any centralised management mechanism. The topology of these networks can be very dynamic due to the mobility of mobile nodes. Under such changeable network topology, multicasting in mobile ad hoc networks is more challenging than in the internet. In this paper, we propose a new multicast routing protocol, named weight-based clustering multicast routing protocol (WCMRP), for mobile ad hoc networks. The goal of this work is to improve multicasting performance in mobile ad hoc networks by efficient use of the available knowledge of the network. Simulation results show our protocol can reduce the overhead and packet losses compared to the On-demand Multicast Routing Protocol (ODMRP).